Sacco & Vanzetti - Montaldo, Giulano, 1930-; Volonté, Gian Maria, 1933-1994; Cucciolla, Riccardo; Cusack, Cyril, 1910-1993; Fratello, Rosanna; Keen, Geoffrey, 1916-2005 (Unidis SRL, 1971)
Η αληθινή ιστορία δύο Ιταλών μεταναστών στις ΗΠΑ, που καταδικάστηκαν άδικα σε θάνατο, για καθαρά πολιτικούς λόγους.